2021
DOI: 10.1016/j.xjon.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of delaying transcatheter aortic valve replacement for the treatment of aortic stenosis in the era of COVID-19

Abstract: Objective The aim of this study was to model the short term and 2-year overall survival for intermediate- and low-risk patients with severe symptomatic AS undergoing timely or delayed transcatheter aortic valve replacement during the 2019 novel coronavirus pandemic. Methods We developed a decision analysis model to evaluate two treatment strategies for both low-risk and intermediate-risk patients with aortic stenosis during the 2019 novel coronavirus pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Patients awaiting structural heart disease (SHD) interventions constitute a particularly challenging group, as many have conditions that might be life threatening if the intervention is inappropriately delayed [ 25 •, 26 – 29 ]. Studies have shown a decline in surgical and transcatheter aortic valve procedures during the pandemic with potential increase in mortality [ 24 , 25 •, 26 – 29 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients awaiting structural heart disease (SHD) interventions constitute a particularly challenging group, as many have conditions that might be life threatening if the intervention is inappropriately delayed [ 25 •, 26 – 29 ]. Studies have shown a decline in surgical and transcatheter aortic valve procedures during the pandemic with potential increase in mortality [ 24 , 25 •, 26 – 29 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The investigators found that prompt TAVR resulted in improved 2-year overall survival compared with delayed intervention for intermediate- and low-risk patients; as delayed treatment was associated with death and need for urgent/emergent TAVR during the waiting period. In contrast, when the probability of acquiring COVID-19 was significant (> 55% for intermediate-risk patients or 47% for low-risk patients), delayed TAVR was favored over prompt intervention [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations